Catalytic Enantioselective Synthesis of Cyclobutenes from Alkynes and Alkenyl Derivatives - Parsutkar, Mahesh M. (J Am Chem Soc, 2019)
Discovery of enantioselective catalytic reactions for the preparation of chiral compounds from readily available precursors, using scalable and environmentally benign chemistry, can greatly impact their design, synthesis and eventually manufacture on scale. Functionalized cyclobutanes and cyclobutenes are important structural motifs seen in many bioactive natural products and pharmaceutically relevant small molecules. They are also useful precursors for other classes of organic compounds such as other cycloalkane derivatives, heterocyclic compounds, stereo-defined 1,3-dienes and ligands for catalytic asymmetric synthesis. The simplest approach to make cyclobutenes is through an enantioselective [2+2]-cycloaddition between an alkyne and an alkenyl derivative, a reaction which has a long history. Yet known reactions of this class that give acceptable enantioselectivities are of very narrow scope and are strictly limited to activated alkynes and highly reactive alkenes. Here we disclose a broadly applicable enantioselective [2+2]-cycloaddition between wide variety of alkynes and alkenyl derivatives, two of the most abundant classes of organic precursors. The key cycloaddition reaction employs catalysts derived from readily synthesized ligands and an earthabundant metal, cobalt. Over 50 different cyclobutenes with enantioselectivities in the range of 86–97% ee are documented. With the diverse functional groups present in these compounds, further diastereoselective transformations are easily envisaged for synthesis of highly functionalized cyclobutanes and cyclobutenes. Some of the novel observations made during these studies including a key role of a cationic Co(I)-intermediate, ligand and counter ion effects on the reactions, can be expected to have broad implications in homogeneous catalysis beyond the highly valuable synthetic intermediates that are accessible by this route.